Systemic infection drives urgent care needs and outcome in adults with long-term neurological conditions - Ana Saldanha Ramos; Ian Galea; Aravinthan Varatharaj (Brain, Behavior, & Immunity - Health, 2022)
It is estimated that 1 in 6 people are living with a long-term neurological condition (LTNC). Although it is likely that systemic infections are a common trigger for urgent tertiary care needs in LTNCs, there is a lack of data. Yet this is important since systemic infections are a modifiable risk factor, and hence the motivation for a formal evaluation. We undertook case note review of 155 consecutive unselected adult patients with LTNC receiving urgent care at a tertiary hospital between November and December 2019. Data were collected on presenting symptoms, diagnosis, length of stay, complications, and change in social needs. The most common LTNCs were neurocognitive disorders (n = 68, 44%), cerebrovascular disorders (n = 65, 42%), and epilepsy (n = 19, 12%). Respiratory infections were most common (n = 40, 62.5%), followed by urinary (n = 16, 25%), skin (n = 4, 6%), gastrointestinal (n = 3, 5%) and bone (n = 1, 1.5%). Systemic infection was the trigger for urgent care in 41.3% of patients and in multivariable regression was associated with an increased likelihood of admission (p < 10−5, OR = 7.8, Nagelkerke R2 = 0.37), longer length of stay (p = 0.03, β = 5.91, R2 = 0.06), and death (p = 0.045, OR = 4.3, Nagelkerke R2 = 0.22). Altered mental status was the presenting symptom most frequently associated with infection (p < 10−8, χ2 test). In conclusion, systemic infections are a major trigger of acute tertiary care needs in adults with LTNCs, and play a role in determining clinical outcome. Since systemic infections are preventable or can be treated if identified early, they may represent a modifiable target to improve quality of life, clinical outcomes and health service efficiency.